Peran Politik dalam Pengembangan Ekonomi Syariah di Indonesia - Nawaliyah Nawaliyah; Indah Kurnia Fitasari; Ismah Thayyibah Hanun; Mashudi Mashudi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to analyze the role of political economy in the development of sharia economics, with a focus on government policies and political dynamics that influence this sector. Despite progress, challenges such as the public's lack of understanding of Islamic financial products and inadequate regulations still need to be addressed. With a qualitative approach, this research reveals strategies that can increase sharia economic growth in the future, as well as the importance of synergy between government policies and public awareness of sharia values.